The effect of rearing methods on qualitative and quantitative parameters of ewe milk yields - Wazna E.; Gut A.; Wójtowski J. (Production systems and product quality in sheep and goats, 2001)
Two milking methods were adopted in ewes coming from two dairy lines: I) ewes milked (2nd-6th months of lactation), (2nd month: lambs suckled 12 hours, and the following 12 hours they were milked once a day. At the end of the 3rd month lambs were weaned and ewes were milked twice a day). II) ewes milked after weaning lambs, (3rd-6th months of lactation). On the basis of control milkings in the 3rd, 4th, 5th and 6th months of lactation, physical and chemical properties and the hygienic quality of milk were compared. No effect of the lamb rearing method and the ewes genotype was found on the milking performance and qualitative traits of milk during the 4-month period of lactation after weaning. Ewes milked from July to November showed performance 33 per cent higher than the ones milked from February to June.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)